Directional extraction and penetration of phosphorene nanosheets to cell membranes. Issue 4 (21st January 2020) - Zhang, Wei; Chen, Yezhe; Huynh, Tien; Yang, Yunqiu; Yang, Xianqing; Zhou, Ruhong
Abstract : The extracted phospholipid molecules are aligned along the wrinkle direction of the phosphorene nanosheet and small phosphorene nanosheets penetrate into cell membrane in a specific direction. Abstract : Recently, phosphorene, a novel two-dimensional nanomaterial with a puckered surface morphology, was shown to exhibit cytotoxicity, but its underlying molecular mechanisms remain unknown. Herein, using large scale molecular dynamics simulations, we show that phosphorene nanosheets can penetrate into and extract large amounts of phospholipids from the cell membranes due to the strong dispersion interaction between phosphorene and lipid molecules, which would reduce cell viability. The extracted phospholipid molecules are aligned along the wrinkle direction of the phosphorene nanosheet because of its unique puckered structure. Our results also reveal that small phosphorene nanosheets penetrate into the cell membrane in a specific direction which is determined by the size and surface topography of phosphorene and the thickness of the membrane. These findings might shed light on understanding phosphorene's cytotoxicity and would be helpful for the future potential biomedical applications of phosphorene, such as biosensors and antibacterial agents.